Conservação do papagaio-galego Alipiopsitta xanthops no estado de São Paulo : estudo de uma população in situ e análises comportamentais em cativeiro e vida livre - Beltrame, Luisa Bontorin (2017)
The Cerrado biome is a brazilian hotspot included among the most endangered biomes in the world. The Yellow-faced Parrot (Alipiopsitta xanthops) is one of the parrot species that are suffering with the current alterations on the biome. This species is endemic of the brazilian Cerrado and was once considered probably extinct in the state of São Paulo. Species conservation strategies should consider ex situ and in situ approaches. Therefore, this study intended to enlarge the in situ and ex situ knowledge about the Yellow-face Parrot in the state of São Paulo, aiming to stablish the minimum necessities for the species populations’ management in the remaining habitats in the state, and also provide behavioral information for the species in order to enable the in situ and ex situ management of the species. The in situ studies of the population were made at the municipality of Rifaina, northeastern region of the state of São Paulo, selected after ecological niche modeling results. The fieldwork comprised two field trips of ten days each. Active searches for the species were conducted on the region and the behavioral records were made using the Ad libitum method. The initial ex situ data collection for the species was based on a survey intended to animal-keeper institutions in the states of São Paulo and Minas Gerais. The ex situ behavioral studies were conducted on three animalkeeper institutions in the state of São Paulo, using the Ad libitum method followed by the “Focal Animal” method for quantification. A new occurrence area of the species was identified in the state of São Paulo, and behavioral, populational and dietary information were provided, including the use of anthropized areas for the species. In view of this new area of occurrence for the species and its use of anthropized areas, conservation actions become necessary in order to maintain the minimal conditions for the population maintenance in the region. Considering the ex situ data obtained, reproductive behaviors were recorded in captive animals despite the few occurrences of these behaviors reported by the keeper institutions. This fact, in addition to the record of normal behaviors for the group, elect the species as able to conservation strategies focused on captivity reproduction, in order to maintain backup populations.